Analysis of the Economic Potential of Tobacco Farmers for Community Welfare in Wungurejo Village, Ringinarum District, Kendal Regency - Wahyu Erik Indriyanto; Senja Arum Puspita; M. Roi Bagus H; Fakhrudin Muhammad Arrozi; Puput Nur Maulidiyah; Clarista Marya Ulfa; R. Lena Adzi; Alfandi Alfandi (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2024)
The potential for community welfare in Wungurejo Village, Ringinarum District, Kendal Regency requires alternative strategies for tobacco farming to reduce the risks posed. The government also needs to be actively involved in supporting holistic programs for tobacco farmers in order to achieve sustainable agricultural goals so that economic potential can determine the welfare of the community. This research is qualitative research using data collection methods in the form of interviews, surveys and observations and aims to analyze the economic potential of tobacco farmers on the welfare of the community in Wungurejo village.